2019
DOI: 10.1103/physrevd.100.044044
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields on Kerr spacetime, Hertz potentials, and Lorenz gauge

Abstract: We review two procedures for constructing the vector potential of the electromagnetic field on Kerr spacetime, namely, the classic method of Cohen & Kegeles, yielding A µ in a radiation gauge, and the newer method of Frolov et al., yielding A µ in Lorenz gauge. We demonstrate that the vector potentials are related by straightforward gauge transformations, which we give in closed form. We obtain a new result for a separable Hertz potential H µν such that A µ lor = ∇ ν H µν . * s.dolan@sheffield.ac.ukRecent resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…They fit into Benenti's canonical form (3.8) when the Stäckel matrix φ and its inverseφ are given by 11) and ζ-matrices ζ (µ) are given by…”
Section: Killing Tensor On the Kerr-nut-(a)ds Spacetimementioning
confidence: 99%
“…They fit into Benenti's canonical form (3.8) when the Stäckel matrix φ and its inverseφ are given by 11) and ζ-matrices ζ (µ) are given by…”
Section: Killing Tensor On the Kerr-nut-(a)ds Spacetimementioning
confidence: 99%
“…where of the four free parameters A, B, C, c only three are physical (one can be scaled away) and are related to the mass and two rotations. As per usual, the separability property shown below does not need the special form (21) and occurs "off-shell", for arbitrary functions…”
Section: Black Hole Of Minimal Gauged Supergravitymentioning
confidence: 94%
“…In 2018, Frolov, Krtous, and Kubiznak showed that Lunin's ansatz can be written in a covariant form, in terms of the principal tensor [15,16], allowing them * rcayuso@perimeterinstitute.ca † fgray@perimeterinstitute.ca ‡ dkubiznak@perimeterinstitute.ca § amargalit@perimeterinstitute.ca ¶ rsouza@perimeterinstitute.ca * * lthiele@perimeterinstitute.ca to extend Lunin's result to general (possibly off-shell) Kerr-NUT-AdS spacetimes [17]. The separation of massive vector (Proca) field perturbations in these spacetimes (an achievement previously absent even for the four-dimensional Kerr geometry) followed shortly after that [18], see also [19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…In the shadowless gauge, the softened string singularity is confined to the middle region r min < r < r max . We can understand its form by analyzing the form of T R ab together with the equations ( 56), (57), and (58) for x R ab and the inversion relation…”
Section: Softened String and Regularity Requirementsmentioning
confidence: 99%